PERBANDINGAN KEMAMPUAN MEMBACA PERMULAAN ANTARA METODE SAS (STRUKTURAL ANALITIK SINTETIK) DENGAN METODE GLOBAL BERBANTUAN MEDIA GAMBAR DI KELAS II SDN 045 TARAKAN - Herianti Herianti; Kadek Dewi Wahyuni Andari; Agustinus Tonding Boa (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
This study aimed at determining if there was a difference in early reading ability between learners taught with the Structural Analytic Synthetic (SAS) method which was assisted with image media and those taught with global method which was also assited with image media. This quasi-experimental research was conducted in August 2019. The population was the second grades students of SDN 045 Tarakan. The sample consistedof two classes, class IIA as the experimental group and class IIB as the control group. The independent sample t-test results showed that the value of calculated t was 0,193, the significance level was 0,05, the df was 56, and the critical t was 2.00. it was known that the value of the calculated t was equal or less than that of the critical t. Thus, it was concluded that there was no difference in the result of initial reading ability between second grade learners taught with image media assisted SAS methodand those taught with image media assisted global method at SDN 045 Tarakan.